Functional movement development across the life span - Cech, Donna J. PT, DHS, Certified Specialist in Pediatric physical Therapy (PCS); Martin, Suzanne "Tink" PT, PhD; Staples, William H. PT, DHSc, DPT, Clinical Specialist in Geriatric Physical Therapy (GCS), FAPTA (Missouri Elsevier, 2025)
Evidence-based information on functional movement development, health, and wellness across the life span. Providing a solid foundation in the normal development from both a systems and function perspective, this comprehension resource helps you maximize a patient's functional movement abilities across the life span
1. Functional independence: a lifelong goal -- 2. Theories of development -- 3. Motor development -- 4. Motor control and motor learning -- 5. Skeletal system changes -- 6. Muscle system changes -- 7. Cardiovascular and pulmonary system changes -- 8. Nervous system changes -- 9. Sensory system changes -- 10. Endocrine and integumentary system changes -- 11. Posture, balance, and locomotion -- 12. Prehension -- 13. Health and fitness
Keywords: Motor ability; Motor ability in children